Gujarat, the making of a tragedy - Varadarajan, Siddharth (New Delhi ; New York, NY : Penguin Books, 2002)
Contributed articles and analysis of media reports on the Gujarat tragedy.
Keywords: Communalism -- India -- Gujarat; Riots -- India -- Gujarat; Hindus -- India -- Gujarat; Muslims -- India -- Gujarat; Gujarat (India) -- Ethnic relations